Religious Accountant as Fraud Reducer - Isnan Murdiansyah (International Journal of Religious and Cultural Studies, 2022)
This study aims to reveal the role of accountants' religiosity to reduce fraud. This research employed an interpretive approach with phenomenological methods to portray symptoms around the actors who are organized within the scope of interaction between the accounting profession, clients, and third parties. The data in this study were obtained from observations in the field by actively participating in every activity and in-depth interviews related to efforts to avoid fraudulent practices with people directly involved. Data analysis was carried out using noema and noesis analysis. The study indicates that accountants' religiosity must be carried out by combining the culture of professionalism and applying it to their work.